Larval and female footprints as feeding deterrent cues for immature stages of two congeneric ladybird predators (Coleoptera: Coccinellidae). Issue 5 (October 2014) - Kumar, B.; Mishra, G.; Omkar
Abstract In the present study predation parameters, i.e. consumption rate, conversion efficiency and growth rate, and total developmental duration of immature stages of two congeneric ladybirds, Coccinella septempunctata (L.) and Coccinella transversalis F., have been evaluated in presence of conspecific and heterospecific fourth instar larval and adult female tracks. We hypothesized that the semiochemicals within larval/adult female tracks might act as foraging/feeding deterrent pheromones (FDPs) and would reduce the predation parameters; and would prolong total developmental duration of ladybird predators. Results of the study positively affirmed our hypothesis. The deterrence in prey consumption and reduction in conversion efficiency and growth rate was density dependent with species-specific variations. Consumption rate, conversion efficiency, and growth rate of larval instars decreased and the total developmental duration of immature stages increased when exposed to an increasing density of zero, two, three, and four conspecific/heterospecific larval/adult female tracks. Between ladybird species, C. septempunctata had higher consumption rate, growth rate, and total developmental durations, whereas conversion efficiency was higher in C. transversalis. Despite the presence of semiochemical tracks as foraging barriers, early instars showed higher conversion efficiencies and growth rates, whereas fourth instars had highest consumption rate in all experimental treatments. The present study, therefore, suggests that semiochemical tracks significantly reduce the predation potential and prolong developmental duration of conspecifics and heterospecifics. They, thus behave as FDP.